Non-fatal injuries among Chinese aged 65 years and older: findings from the Fourth National Health Services Survey. Issue 4 (30th June 2010) - Hu, Guoqing; Rao, Keqin; Baker, Susan P
Abstract : Objective: To understand the epidemiology of non-fatal injuries among adults aged 65 years and older in China. Design: Cross-sectional survey (the Fourth National Health Services Survey of China). Participants: Urban and rural residents aged 65 years and older from 56 400 households in China. Main Outcome Measures: The incidence rate was calculated as the number of persons injured in the previous 12 months divided by the population×1000. Results: The incidence rate of non-fatal injuries among elderly individuals in the previous 12 months was 37.5 per 1000 population. Home, street, working environment, and public buildings were the most common places of occurrence, accounting for more than 90% of injuries. Falls were the leading cause of non-fatal injuries. After adjusting for other factors, Han people were 39% more likely to be injured than non-Han people, and the divorced and the widowed were found to have, respectively, 4.6 and 2.2 times the risk of injury compared with single persons, p<0.05. Education, per capita household income and urbanisation did not significantly affect the injury risk when confounding factors were controlled for. Conclusion: Almost 4% of adults aged 65 years and over sustain injuries each year in China. Falls should be a priority of injury prevention for elderly people, efficient home injury prevention programmes need to be developed, and the divorced and widowed should be targeted as groups at high risk of injury.